2019
DOI: 10.3390/ma12111789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Curing Method on the Mechanical Strength of Alkali-Activated Slag Mortar after High-Temperature Exposure

Abstract: The aim of this work was to study the mechanical strength and microstructure changes of alkali-activated slag mortar (AAS mortar) after being heat treated in the temperature range of 200–1000 °C. The AAS mortar was cured in the ambient condition (20 ± 5 °C, 60 ± 5% RH) (Relative humidity: RH) and high temperature condition (80 °C) for 27 days with three different heating regimes: curing in a dry oven, curing in sealed plastic bags, and in a steam environment. The activator for the AAS synthesis was a mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The mechanical strength of the mortar mixes was reported to decrease as the temperature increased, and a higher reduction was observed at higher temperatures. The strength reduction was due to the cracking in the mortar matrix, confirmed by the Scanning Electron Microscope (SEM) analysis of each mix after exposure to the elevated temperatures [ 20 ]. Another study carried out by Tran and Kwon [ 21 ] noted that alkali-activated slag mortar was sensitive to elevated temperatures (200, 400, 600, 800, 1000 and 1200 °C), and the reduction in the mechanical strength varied dependent on the percentage of Na 2 O present in the mortar mixes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical strength of the mortar mixes was reported to decrease as the temperature increased, and a higher reduction was observed at higher temperatures. The strength reduction was due to the cracking in the mortar matrix, confirmed by the Scanning Electron Microscope (SEM) analysis of each mix after exposure to the elevated temperatures [ 20 ]. Another study carried out by Tran and Kwon [ 21 ] noted that alkali-activated slag mortar was sensitive to elevated temperatures (200, 400, 600, 800, 1000 and 1200 °C), and the reduction in the mechanical strength varied dependent on the percentage of Na 2 O present in the mortar mixes.…”
Section: Introductionmentioning
confidence: 99%
“…Natarajan et al [19] studied the residual compressive and flexural strength of selfcompacting mortar made with different replacement percentages (10,20,30,40 and 50%) of natural sand by glass powder after exposure to elevated temperatures (200, 400, 600, 800, 1000 and 1200 • C) at a heating rate of 20 • C/min. The authors found that the compressive and flexural strength decreased with an increase in temperature, and it was more pronounced for the mortar made with higher glass powder content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AAMs could be useful as concrete binders, bricks, or lightweight insulation materials, the physical properties are strongly affected by the source material, alkaline activators, and the processing parameters. Most of the factors that influence the microstructural evaluation and/or mechanical properties of AAMs have, however, already been studied, including the chemical and physical properties of raw materials ( Fernandez-Jimenez et al, 2006 ; Traven et al, 2019 ; Rajamma et al, 2012 ), Al/Si (composition) ratios ( van Jaarsveld et al, 2002 ), the activator ( Chen et al, 2017 ), curing regime and aging ( Češnovar et al, 2019a ; Tran et al, 2019 ), and the microstructure and phase composition ( Khale and Chaudhary, 2007 ; Ismail et al, 2014 ). Despite numerous studies regarding the alkali activation process, there is still a lack of knowledge regarding defects in the matrix and methods to evaluate possible causes.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting foams exhibited values for water absorption, apparent density, and compressive strength of approximately 126.5%, 0.414 g/cm 3 , and 6.76 MPa, respectively. Results from other researchers to date have nevertheless shown that the stability of foams at high temperatures (especially with regard to shrinkage) is strongly affected by the composition of raw materials, not only when fly ash is used (Martin et al, 2015) but also when other additives such as metakaolin and slag are present in the AA material (Mierzwinski et al, 2019;Tran et al, 2019). Some of the authors concluded that shrinkage occurs due to the increased density or change in volume induced by the crystallization of new phases, rather than due to a melting point or viscous creep (Martin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%